The End of Multilateralism? Rising Regional Trade Agreements, Trade Wars, and The Future of the International Trading System - Derya Hekim (European Scientific Journal, ESJ, 2026)
The multilateral trading system, consolidated through the World Trade Organization (WTO), faces an existential crisis driven by three mutually reinforcing dynamics: the structural failings and deliberate paralysis of the WTO, most acutely manifested in the Appellate Body’s incapacitation since December 2019; the exponential proliferation of regional trade agreements (RTAs); and two waves of unprecedented trade wars under the Trump administration in 2018–2020 and 2025–2026 that have systematically eroded the rules-based trading order. The COVID-19 pandemic deepened these fractures by exposing supply-chain vulnerabilities and legitimising economic nationalism. While a substantial body of scholarship addresses each of these phenomena in isolation, no existing study integrates all three within a single comparative analytical framework that also encompasses the 2025–2026 second Trump trade war — the most disruptive tariff episode since the Smoot-Hawley era, culminating in a landmark Supreme Court ruling that struck down the legal basis of the tariffs themselves. This study fills that gap by developing an integrated framework that analyses the three phenomena as a self-reinforcing cycle of institutional erosion, drawing on terms-of-trade theory, the deep-agreements literature, and the welfare economics of trade wars. The study reaches four principal conclusions. First, the WTO’s crisis is structural, not cyclical, and cannot self-correct without deliberate institutional reform, most urgently the restoration of appellate dispute settlement. Second, RTAs are not inherently stumbling blocks or building blocks: their welfare and systemic effects depend critically on their depth — shallow and asymmetric agreements impose costs on weaker parties and undermine multilateral norms, while deep agreements that govern investment, regulation, and services can complement them. Third, the future trading system is most plausibly a tiered architecture in which deep regional agreements govern commercially significant trade, a residual WTO framework provides a normative baseline, and bilateral managed trade fills governance gaps — an architecture that is already visible but fragile. Fourth, technology export controls and critical mineral restrictions represent a new and ungoverned category of trade barrier for which neither existing WTO rules nor current RTAs provide effective discipline, constituting the most significant emerging threat to any future trading framework.